The evolution of an active solitary idiopathic choroiditis (focal scleral nodule): a case report of the natural course and a review of the literature - Feng, Yilin; Conrady, Christopher D.; Demirci, Hakan (BMC ophthalmology, 2021)
Background To describe the clinical course of an active solitary idiopathic choroiditis (focal scleral nodule) that nearly resolved over six weeks without intervention. Case presentation An 18-year-old man presented to the emergency department with headaches and new onset central scotoma in the right eye. Visual acuity was 20/20 in both eyes. Fundus examination revealed an amelanotic choroidal lesion with associated shallow subretinal fluid. It measured 6.1 × 6.3 × 1.4mm on A- and B-scan. Evaluation for systemic inflammatory and infectious diseases was negative. A week later, the lesion remained stable, and a month later, there was improvement of the lesion with a decrease in size on OCT and exam and resolution of the subretinal fluid suggesting that the lesion had become inactive. Conclusions Solitary idiopathic choroiditis (Focal scleral nodule) is a rare condition characterized by inflammatory granulomatous reaction. This case report sheds light on the unknown natural course of a solitary idiopathic choroiditis (focal scleral nodule).